Simulation of TiO2/CuO solar cells with SCAPS-1D software. (19th June 2019) - Sawicka-Chudy, P; Starowicz, Z; Wisz, G; Yavorskyi, R; Zapukhlyak, Z; Bester, M; Głowa, Ł; Sibiński, M; Cholewa, M
Abstract: TiO2 /CuO and TiO2 /Cu2 O solar cells are promising devices for photovoltaic applications. The power conversion efficiency of these cells, however, remains low. We used the SCAPS-1D program to perform simulations of n-TiO2 /p-Cu2 O and n-TiO2 /p-CuO thin-film solar cells. The short circuit current and efficiency were 13.3 mA cm −2, 28.4 mA cm −2 and 13.7% 22.4%, respectively, Furthermore, we evaluated some specific parameters of n-TiO2 /p-CuO heterostructure, such as the influence of temperature, interface state density, metal work function, electron and hole capture cross-section, shallow uniform donor density (ND ) for TiO2 with constant uniform acceptor doping density (NA ) in CuO and shallow uniform acceptor density (NA ) for CuO with constant (ND ) in TiO2 . Our findings revealed that the efficiency of n-TiO2 /p-CuO solar cells can be improved by increasing metal work function of the contact and by decreasing defects and the electron and hole capture cross-section.